2016
DOI: 10.1039/c6py00212a
|View full text |Cite
|
Sign up to set email alerts
|

Benzobisthiadiazole-alt-bithiazole copolymers with deep HOMO levels for good-performance field-effect transistors with air stability and a high on/off ratio

Abstract: Two benzobisthiadiazole-alt-bithiazole copolymers were designed and synthesized, and the resulting transistors achieved high performance with air stability and a high on/off ratio.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 48 publications
(97 reference statements)
0
21
0
Order By: Relevance
“…More intriguingly, the corresponding 3MT‐Th‐based devices exhibited a superior shelf‐life time of over 1000 h without any decrement in the PSC initial parameters. The excellent shelf‐life time results from the large bandgap energy, the low‐lying HOMO energy levels, and the robust morphology . It is unambiguously demonstrated that 3MT‐Th is a promising new acceptor unit for organizing the polymer structure used for high‐performance nonfullerene‐type PSCs.…”
Section: Introductionmentioning
confidence: 89%
“…More intriguingly, the corresponding 3MT‐Th‐based devices exhibited a superior shelf‐life time of over 1000 h without any decrement in the PSC initial parameters. The excellent shelf‐life time results from the large bandgap energy, the low‐lying HOMO energy levels, and the robust morphology . It is unambiguously demonstrated that 3MT‐Th is a promising new acceptor unit for organizing the polymer structure used for high‐performance nonfullerene‐type PSCs.…”
Section: Introductionmentioning
confidence: 89%
“…The HOMO energy levels of the four copolymers are all suitable for hole injection and transport . P(BBT‐20‐TET) and P(BBT‐Si‐TET) have deeper HOMO energy levels than P(BBT‐20‐TVT) and P(BBT‐Si‐TVT) due to the larger electronegativity of TET unit, implying that P(BBT‐20‐TET) and P(BBT‐Si‐TET) may have better air stability than P(BBT‐20‐TVT) and P(BBT‐Si‐TVT) . The lowest unoccupied molecular orbital (LUMO) energy levels are calculated from the onset of the reduction peaks, and their LUMO energy levels are in the range of −3.97 to −4.14 eV.…”
Section: Resultsmentioning
confidence: 99%
“…The lowest unoccupied molecular orbital (LUMO) energy levels are calculated from the onset of the reduction peaks, and their LUMO energy levels are in the range of −3.97 to −4.14 eV. The deep LUMO energy levels of the four polymers are suitable for electron injection …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, some benzoazole fused rings with stronger quinoid effects than BT and BTAZ, e.g., benzo[1,2‐ c ;4,5‐ c ′]bisthiadiazole (BBT) and [1,2,5]thiadiazolo[3,4‐ f ]benzotriazole (TBZ) owning two azole rings fused to a benzene ring, have been used successfully to construct conjugated polymers with very narrow bandgaps and high charge carrier mobilities. [ 52–56 ] Such characteristics are appealing for their photovoltaic applications. Unfortunately, to our best knowledge, efficient NFAs containing BBT and TBZ units have been rarely reported.…”
Section: Introductionmentioning
confidence: 99%